Epigenetic Regulation of miRNA Expression in Malignant Mesothelioma: miRNAs as Biomarkers of Early Diagnosis and Therapy - Tomasetti, Marco; Gaetani, Simona; Monaco, Federica; Neuzil, Jiri; Santarelli, Lory (Frontiers in Oncology, 2019)
Asbestos exposure leads to epigenetic and epigenomic modifications that, in association with ROS-induced DNA damage, contribute to cancer onset. Few miRNAs epigenetically regulated in MM have been described in literature; miR-126, however, is one of them, and its expression is regulated by epigenetic mechanisms. Asbestos exposure induces early changes in the miRNAs, which are reversibly expressed as protective species, and their inability to reverse reflects the inability of the cells to restore the physiological miRNA levels despite the cessation of carcinogen exposure. Changes in miRNA expression, which results from genetic/epigenetic changes during tumor formation and evolution, can be detected in fluids and used as cancer biomarkers. This article has reviewed the epigenetic mechanisms involved in miRNA expression in MM, focusing on their role as biomarkers of early diagnosis and therapeutic effects.